(untitled) (Revista Multi-Ensayos, 2019)
Nowadays during the process of training students, mainly in Public Accounting and Finance, it is necessary to manage the environments, and modules that set up an accounting software. During the first semester 2018, the use of this system was proposed, in addition in this essay, the lived experience, difficulties, and achievements are shared. We worked with a group of 41 students of accounting and had the support of assisting students, who were helpful for the success of this subject. I hope that when reading this essay you can perceive the satisfaction that as a teacher of UNAN-Managua, FAREM-Estelí, it was experienced, clearly we will continue working with new strategies so that the learning development of students will improve.